Diagnóstico da pesca extrativista no estado de Roraima: análise socioeconômica no Município de Boa Vista - Silva Junior, Everaldo Ramos da (2015)
This research aimed to characterize the extractive fishing in the state of Roraima, specifically in the city of Boa Vista. To this end it was approached socioeconomic aspect that activity includes within the level of importance that the fishing industry presents to the Amazon population. Secondary objectives addressed the following issues: socioeconomic profile of professional fishermen of the city Boa Vista, employment and income in the fishing sector and their impact on the local economy and the impact of the fisheries sector in the Gross Domestic Product (GDP) of the state of Roraima. The main results indicated that there are no data necessary for a full analysis of the fishing sector in the state of Roraima and lack public policies that can bring due importance to the sector, which has fundamental importance for the local economy. To achieve the proposed objectives was held field research and literature that supported this research, whose data were interpreted in this thesis.